If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3z + -3) = 18 Reorder the terms: 4(-3 + 3z) = 18 (-3 * 4 + 3z * 4) = 18 (-12 + 12z) = 18 Solving -12 + 12z = 18 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 12z = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 12z = 18 + 12 12z = 18 + 12 Combine like terms: 18 + 12 = 30 12z = 30 Divide each side by '12'. z = 2.5 Simplifying z = 2.5
| (2x-17)/5=-5 | | -11=3(v-7)-8v | | 13+x+2x=6x+1 | | 4x^2+8x+36=0 | | 73/100=81 | | 4x+4+8+2x=3(x+5) | | 3u^2+17u+24=0 | | 4x+6(x+2)=35 | | (5x-3)/9=-2 | | 2/3x5/6x14x18 | | -8(3x+1)-4=11 | | 3000(x+100)=2000(x-100) | | -4-8y=35 | | 2(x-5)(x+4)=0 | | 2x-5+8x=7-4x-12 | | 2(14+2x)=8(2+x) | | 2•1/3•3.14•25•25•25 | | 2u^2+15u+28=0 | | 4x+9x-34=68-4x | | -14=-3x | | 3x+7=5x+1-x | | 10/12*1/4= | | y=log^4(3x+11)-5 | | 6.1-0.25(x-8)=0.7x+0.3(x-3) | | 8y+9=6y+14 | | 4(.5-.25y)+y=2 | | 5e^2x=13 | | 12/x^2-4 | | 6x-4+2=3a+1 | | 5-m=113 | | 7-2y=1ty | | -7/10:21/20 |